Pengaruh Pengalaman Kerja, Kompetensi, dan Etika Profesi Terhadap Kualitas Hasil Audit Pada KJA (Kantor Jasa Akuntansi) di Kota Semarang (Studi Kasus Pada Karyawan KJA di Kota Semarang) - Zafira Windasafitri; Noor Salim (Jurnal Rekognisi Akuntansi, 2022)
The purpose of this study was to analyze the Effect of Work Experience, Competence, and Professional Ethics on the Quality of Audi Results. The independent variables analyzed in this study are Work Experience, Competence, and Professional Ethics, and Quality of Audit Results as the dependent variable. The sample used in this study consisted of 100 employees of KJA (Accounting Services Office) in the city of Semarang. Sampling was done by purposive sampling method by distributing questionnaires. The data analysis in this study used validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, feasibility tests of a model (F test), individual parameter significance tests (t statistical tests), and coefficient of determination test (R2). ) with the help of the SPSS program. The results showed that work experience had a positive and significant effect on the quality of audit results, competence had a positive and significant effect on the quality of audit results, and professional ethics had a positive and significant effect on the quality of audit results.